Radiographers' perception on the provision of psychosocial support for cancer patients. (22nd July 2023) - Azzopardi, Jade; Mercieca, Susan; Portelli, Jonathan Loui
Abstract: Introduction: Therapeutic radiographers are the first point of contact for cancer patients undergoing radiotherapy treatment and therefore have an important role in providing both physical and psychosocial support to these patients. This study aimed to evaluate therapeutic radiographers' perception about their role in identifying and providing psychosocial support for patients receiving RT treatment. Method: The study used a cross-sectional, prospective research design. A self-designed questionnaire was distributed to all therapeutic radiographers ( n = 26) working at a radiotherapy department in Malta. Results: A total of 21 therapeutic radiographers completed the questionnaire. All participants felt that the provision of psychological care was an important part of their role as therapeutic radiographers. The majority of the participants reported having the most confidence in giving treatment-related symptoms advice rather than psychological support. The most common barrier to providing psychological support was lack of training (95·2%), followed by the lack of an appropriate screening tool (85·7%), availability of private space to talk to patients (76·2%) and a lack of knowledge (61·9%). Conclusion: While most therapeutic radiographers believed that providing psychosocial support was an important aspect of their role, several barriers prevented them from fulfilling this role. Training, the introduction of a psychosocial screening tool and clear referral processes are recommended to improve radiotherapy service.